Between prison : - Morris, Norval (Oxford University Press, 1990)
In recent years both the "rehabilitation model" of sentencing and the "lock 'em up" approach to punishment have failed to stand up to evaluative research. These two well-known criminologists propose greater reliance upon such intermediate sentencing alternatives as fines, house arrest, community service, and combinations of such alternatives. This will be an important addition to the conservative criminological literature of recent years, and will undoubtedly be widely discussed and reviewed for the next few years